Effects of Illegal Behavior on the Financial Performance of US Banking Institutions - Zeidan, Mohamad Jamal (2013)
This study investigates whether financial performance is affected by corporate violations of laws and regulations. In a sample of 128 publicly traded banks that were subject to enforcement actions by US regulatory authorities over a 20-year period, we observed a significant negative market reaction pursuant to the violations. However, the market reaction did not vary meaningfully in accordance with the severity or repetitiveness of the violation. The results of this study are in conformity with previous research on industries other than banking, notably with regard to negative market reaction. This confirms that shareholders in the banking industry react in a manner considerably similar to their counterparts in other industries.
Keywords: Regulations; Banking Industry; Financial Performance; Violations